2019
DOI: 10.1111/joa.12933
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical hypothesis of septal aperture formation tested in an early medieval population from Ostrów Lednicki (Poland)

Abstract: The aetiology of septal aperture formation is still an open question. The influence of bone robusticity, osteoarthritis, osteoporosis, and the size and shape of ulnar processes has been discussed. Some researchers have shown that weaker muscles lead to greater joint hypermobility, the impingement of ulnar processes on the humeral lamina, and, consequently, septal aperture formation. Assuming this theory is correct, the question is whether flexion or extension or both play a role in septal lamina perforation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 46 publications
(117 reference statements)
0
12
0
3
Order By: Relevance
“…Previous studies reported that individuals with the OAH might present overextension in lax and very mobile elbow joint [1]. This hyperextension may be accounted on increased elasticity of the collagen fibers [13] or weaker triceps [23], but not on the size of the proximal ulna [13], as well as not on the strength of brachialis, which may indicate a supposed dominant role of the olecranon process in the OAH formation [23].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that individuals with the OAH might present overextension in lax and very mobile elbow joint [1]. This hyperextension may be accounted on increased elasticity of the collagen fibers [13] or weaker triceps [23], but not on the size of the proximal ulna [13], as well as not on the strength of brachialis, which may indicate a supposed dominant role of the olecranon process in the OAH formation [23].…”
Section: Discussionmentioning
confidence: 93%
“…Some nonpathological morphological variants, such as os acromiale , have been considered as possible activity‐related changes (Stirland, 1984). In most of the cases, multifactorial aetiology and methodological problems (e.g., lack of definitions and standards) make, however, the scoring and the evaluation difficult (White et al, 2012); We selected two commonly used variants of the humerus, namely, the supracondylar spur and septal aperture that are assumed to be—among others—activity‐related (e.g., White et al, 2012; Myszka, Kubicka, & Tomczyk, 2019). Our aim was to test whether these variants are specific to the armed group.…”
Section: Methodsmentioning
confidence: 99%
“…Within this group, 135 adult femurs, which belonged to 38 females (38 left and 38 right femurs) and 33 males (29 left and 30 right femurs), were available for the current study. Inhabitants of this settlement complex relied mainly on agriculture and partly on breeding domestic animals such as pigs, goats, chickens [12,19]. This was a homogeneous population in terms of socioeconomic structure, with a division of labor wherein females were responsible for raising children, weaving, helping in the harvest, and breeding animals in turn, with male activities focused on lowing, harvesting, and building operations [12].…”
Section: Population Groupsmentioning
confidence: 99%